Effects of different overwintering conditions on spring phenology of the seasonal leaves of different woodland strawberry (Fragaria vesca) genotypes - Liu, Zhenzhen (Helsingin yliopisto, 2022)
Woodland strawberry (Fragaria vesca) is a perennial herb in the Rosaceae family with dimorphic leaves, summer and winter leaves, adapted to seasonal climate. Woodland strawberry produces a new set of leaves in spring that are photosynthetically active throughout the summer season (summer leaves), and the leaves senescence in autumn when they are replaced by a new set of leaves (winter leaves). The winter leaves retain photosynthetic capacity under the snow cover throughout the winter season, which prolong the photosynthetic period of the species. With the world-wide climate warming, the thickness of winter snow is decreasing, which can affect overwintering and spring phenology of plants. This thesis focuses on springtime ecophysiology and phenology of the senescing winter leaves and the formation of new summer leaves of woodland strawberry genotypes of different European origin. The 15 different genotypes of woodland strawberry are from Iceland, Italy and Norway, and they originate from different environments that are geographically separated from each other, so the populations are genetically distinct. In this study, these genotypes were kept at two different overwintering sites, coastal site at the Åland islands with mild temperatures, and continental site in Lammi with a persistent snow cover. According to the results all 15 genotypes showed earlier development of the summer leaves and earlier senescence of winter leaves in the group with Åland as overwintering site than in the group with Lammi. Another important finding is that the first summer leaves produced in spring begun to senesce shortly after they are fully developed and were replaced by later formed summer leaves. Specifically, the dates of summer leaf formation, flowering and stolon production were advanced, and the dates of winter leaf senescence were also advanced. The value of different leaf types to chlorophyll fluorescence was also lower at the Åland site. Therefore, it can be concluded that overwintering conditions have an effect on the ...